Establishing Shipyards’ BPR Key CSF’S during Revamping Project Disbursement Process - Ismail, Azman; Osman, NorHasni (International Journal of Engineering and Technology, 2018)
BPR is a great management tools used to revamp a business process within anorganization. Nowadays, most of the organization have reach its maturity stage and adaptation of BPRCSF’s must be scrutinize to ensure that the intended BPR objectives are fulfilled. The Shipyard, whilerevamping its project disbursement process came across with a lot of CSF’s, but only a few are thekey CSF’s that help to move forward with the BPR change initiative. This research used qualitativemethod with interactive Action Research Cycle to identify and establish Shipyard BPR key CSF’s forits BPR project. The finding was made using Force Field Analysis between Shipyard BPR teammembers and the established BPR key CSF’s which will help to further understand how to implementBPR project effectively and successfully without incurring further delay in cost and time to theShipyard.
Keywords: BPR; BPR CSF’s; BPR key CSF’s; effective top management support; effective communications; effective training; employee’s involvement; employee’s empowerment.